2023
DOI: 10.3390/ijms241311211
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Diurnal and Nocturnal-Warmed Plants, the Molecular Mechanism Underlying Cold Deacclimation Response in Deschampsia antarctica

Abstract: Warming in the Antarctic Peninsula is one of the fastest on earth, and is predicted to become more asymmetric in the near future. Warming has already favored the growth and reproduction of Antarctic plant species, leading to a decrease in their freezing tolerance (deacclimation). Evidence regarding the effects of diurnal and nocturnal warming on freezing tolerance-related gene expression in D. antarctica is negligible. We hypothesized that freezing tolerance-related gene (such as CBF-regulon) expression is red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…When the effect of daytime and nocturnal warming on the genetic expression of D. antarctica under laboratory conditions was evaluated, it was determined that only nocturnal warming can downregulate the genes related to freezing tolerance. On the contrary, nocturnal warming induced genes related to growth promotion and carbon assimilation, which induce cold deacclimatization in D. antarctica [38]. These results further support the idea that nocturnal rather than diurnal warming favors the deacclimatization response to cold in D. antarctica.…”
Section: Consequences Of Warming On the Ecophysiology Of Antarctic Va...supporting
confidence: 75%
See 1 more Smart Citation
“…When the effect of daytime and nocturnal warming on the genetic expression of D. antarctica under laboratory conditions was evaluated, it was determined that only nocturnal warming can downregulate the genes related to freezing tolerance. On the contrary, nocturnal warming induced genes related to growth promotion and carbon assimilation, which induce cold deacclimatization in D. antarctica [38]. These results further support the idea that nocturnal rather than diurnal warming favors the deacclimatization response to cold in D. antarctica.…”
Section: Consequences Of Warming On the Ecophysiology Of Antarctic Va...supporting
confidence: 75%
“…[35][36][37]. Recently, in a laboratory study, López et al [38] evaluated for the first time the gene expression of cold-acclimated D. antarctica plants. They reported that cold-acclimated plants showed significant enrichment in genes related to transporter activity and membrane structure, such as UDP-glycosyltransferase activity.…”
Section: Deschampsia Antarctica Colobanthus Quitensismentioning
confidence: 99%
“…Desv.)) revealed that the deacclimation process had a greater effect in nocturnal-warmed plants [21].…”
Section: Factors That Influence the Phenomenon Of Deacclimationmentioning
confidence: 97%
“…However, it also concerns other species that grow in more extreme temperature conditions, including some trees (e.g., birch, mulberry, pine trees), grasses (e.g., Antarctic hair grass, creeping bentgrass), tea, etc. [18][19][20][21][22]. However, for each of these species the temperature conditions and the periods needed for cold acclimation/deacclimation or reacclimation can differ.…”
Section: Introduction-significance Of Cold Acclimation and Deacclimat...mentioning
confidence: 99%